My sister the apple tree : a refugee story of hope and resilience - Scott, Jordan, 1978-; Saeed, Jamal, 1959- (Random House Studio, 2025)
A young boy forms a deep bond with an apple tree planted on the day of his birth, and after fleeing his homeland, he carries the tree with him to a new home, finding a lasting connection to both places as it grows.